Perymetria krótkofalowa – znaczenie w diagnostyce jaskry w krótkowzroczności - Herba, Ewa; Pojda, Stefan; Zatorska, Barbara; Pojda-Wilczek, Dorota; Makowiecka-Obidzińska, Katarzyna (Klinika Oczna / Acta Ophthalmologica Polonica Supplement, 2004)
The static perimetry is the most useful diagnostic method in glaucoma. The aim of this paper is to compare the results of static short wavelength automatic perimetry (SWAP) with the classic one (white) in myopic patients with and without glaucoma. The Tubingen Automatic Perimeter was used, the threshold strategy within the central 30 degrees and glaucoma program was performed .The sensitivity of the retina in blue on yellow perimetry was nearly two classes lower than in the classic method in both groups. The enlargement of the blind spot and the appearance of the arcuate relative scotomas could be shown in SWAP, while classic perimetry is still normal. Both, the mean defect (MD) and the mean sensitivity (MS) in SWAP indicated for the very early glaucomatous changes in myopic patient, too. The changes of the loss variance (LV) was not characteristic for these patients.